THE STAGES OF SECOND LANGUAGE ACQUISITION: EARLY AGE LANGUAGE PRODUCTION - Sukri, Chintia Dewi; Perangin-Angin, Alemina Br. (Universitas Islam Sumatera Utara, 2024)
Early second language (L2) development plays a crucial role in the academic advancement and social integration of culturally and linguistically diverse children. Particularly in Indonesia, where the dominant Bahasa language differs significantly from their native language (L1), these young learners often encounter challenges in acquiring L2 proficiency. Their language development in the early stages is heavily influenced by their environment and familial context. Despite these factors, lexical errors are commonplace during the initial phases of second language acquisition. This study aims to compare the stages of human language acquisition by analyzing the utterances of children aged two to three who are learning English as their L2 and Bahasa as their L1. The research methodology involved meticulous documentation of the children's speech patterns, with three participants contributing to the investigation. Utilizing tree diagrams, the collected data was meticulously examined to assess the children's language production abilities. The findings revealed that by the age of one, the children had begun acquiring their L2, demonstrating proficiency in both English and Bahasa. Moreover, they displayed the capacity to comprehend and communicate effectively in both languages within the context of their everyday educational experiences.